2022
DOI: 10.1093/ofid/ofac570
|View full text |Cite
|
Sign up to set email alerts
|

Infections Simulating Immune Checkpoint Inhibitor Toxicities: Uncommon and Deceptive

Abstract: Use of Immune checkpoint inhibitors (ICIs), a revolutionary treatment in modern oncology, is frequently complicated by immune-related adverse events (irAEs), which can be confused with infections, and vice versa, thus complicating management decisions. Herein we review the published cases of infections as simulators of irAEs in cancer patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Further, self-destruction of the skin metastatic lesions and the subsequent skin infection may trigger the development of skin irAEs. However, it was reported that the associations with viral and bacterial infections are considered rare and deceptive [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Further, self-destruction of the skin metastatic lesions and the subsequent skin infection may trigger the development of skin irAEs. However, it was reported that the associations with viral and bacterial infections are considered rare and deceptive [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Notably, a hypothesis has been proposed through which infections might in fact be stimulators of irAEs in the absence of immune suppression. Infections can either occur coincidentally or due to a dysregulated immune response provoked by ICIs (36). In this context, such infections have been characterized as "infections due to dysregulated immunity" (36).…”
Section: Ici Administration and Risk Of Infectionmentioning
confidence: 99%
“…Infections can either occur coincidentally or due to a dysregulated immune response provoked by ICIs (36). In this context, such infections have been characterized as "infections due to dysregulated immunity" (36). The Memorial Sloan Kettering Cancer Center study mentioned above demonstrated 10 cases of Clostridioides difficile-associated diarrhea (CDAD) in patients receiving ICIs (7).…”
Section: Ici Administration and Risk Of Infectionmentioning
confidence: 99%